The Role of Traditional Settlement Identity as a Part of Creative Tourism Planning: Case of Wana Village, Lampung - Prameswari, Mariza Barbora; Hardilla, Dini (ASEAN Journal on Hospitality and Tourism, 2024)
Architecture is one of the results of civilization, which expresses a way of life, is passed down from one generation to another, acts as a tradition, and holds cultural values. The cosmological elements possessed by architectural works turn into aesthetic values and form an image of life. Indonesian architecture applies this type of architecture, especially in Wana Village. Wana Village is one of the heritage villages of the Melinting Kingdom, which still keeps its existence as a place for the residents to live. It reflects the local social wisdom of the community and is a vernacular building of tourism value. This study aims to analyze the traditional settlement of Wana Village at the tourism level and develop it as an architectural design innovation. In addition, this study analyzes social, economic, and residential patterns, events/history, and resources that influence the attractiveness of Wana Village as a cultural tourism destination. The sustainability of Wana Village results from a harmonious emotional bond between residents, even though they have differences. It makes Wana Village more valuable for tourists.